Participatory Approach to Community Based Water Supply System - Kenshiro Ogi; Ismu Rini Dwi Ari; Hayeong Jeong; Kakuya Matsushima; Kiyoshi Kobayashi (European Regional Science Association (ERSA), 2010)
Water scarcity due to climate change as well as inappropriate water governance is one of the important topics in the world, particularly in developing countries. Most people who live close to the water resource are not always economically-advantaged. Moreover, it might be seems that people living close to 'economically-attractive water resource' are classified into lower category according to the standard of living in the country. Community based water supply system is one of strong alternatives to existing water supply system by the public sector. The community based water supply system works more effectively if it is based upon strong community network in the region. This study conducts an empirical research on community based water supply system in Indonesian rural area. In this paper, we propose a discrete-choice model which describes the mechanism of resident's spontaneous collaboration to access water. We formulate a hypothesis that households with better community tie have ability to organize "community based" management system. In order to test it, we formulate a spatial probit model which can consider the effect of social interaction upon their choices in water supply system. Traditionally, spatial models are estimated with maximum likelihood method, however, in this paper, we adopt Markov chain Monte Carlo (MCMC) method to estimate parameters due to the difficulty in estimation of discrete-choice model with spatial interaction term. Using dataset from a field survey in Indonesia which we conducted in 2008 the spatial probit model is empirically tested to show that social interaction in the community plays an important role on resident's spontaneous collaboration to manage community-based water supply system.
Keywords: 330